The chaperonins - Ellis, R. J. (Reginald John), 1935- (Cell biology., 1996)
The first of its kind, this volume presents the latest research findings on the chaperonins, the best studied family of a class of proteins known as molecular chaperones. These findings are changing our view of some fundamental cellular processes involving proteins, especially how proteins fold into their functional conformations. Key Features * Origins of the new view of protein folding * Prokaryotic chaperonins * Eukaryotic chaperonins * Evolution of the chaperonins * Refolding of denatured proteins * Organelle biosynthesis * Biomedical aspects.